Planning in the age of acceleration: a perspective on digital inclusion in online urban planning meetings - Mualam, Nir (Frontiers in Sustainable Cities, 2024)
In the age of technological acceleration, new digital shifts and the increased use of ICT have changed the ways we work, live, sleep, and shop. Remarkable transformations have left footprints in the planning world as well, with many urban planners harnessing technology to improve and expedite planning processes. This process accelerated further during the COVID pandemic, which forced many planning committees and local governments to conduct public meetings, hearings, and participatory processes remotely in order to allow the planning machine to continue rolling while abiding by social distancing rules. Developments such as this have been part of a broader shift towards the increasing reliance of planning on video-conferencing and other technological innovations. While this new policy has proved advantageous to many, it has also had regressive impacts and severely affected social inclusion in the planning process. This paper reviews these outcomes by focusing on the Israeli planning system post-COVID, which continues to embrace videoconferencing as a tool in planning. The findings illustrate the vulnerability of certain groups to the accelerated digitalization of urban planning. Despite planners' awareness of these outcomes and adaptations made to existing means of e-participation, online planning meetings are not geared towards using tools and platforms to improve practice; instead, remote participation remains largely a 'pro-developers' process and could marginalize other participants.